A user-friendly NoSQL framework for managing agricultural field trial data - Steven H. Wu; Tristan A. Mueller (Scientific Reports)
Abstract Field trials are one of the essential stages in agricultural product development, enabling the validation of products in real-world environments rather than controlled laboratory or greenhouse settings. With the advancement in technologies, field trials often collect a large amount of information with diverse data types from various sources. Managing and organizing extensive datasets can impose challenges for small research teams, especially with constantly evolving data collection processes with multiple collaborators and introducing new data types between studies. A practical database needs to be able to incorporate all these changes seamlessly. We present DynamoField, a flexible database framework for collecting and analyzing field trial data. The backend database for DynamoField is powered by Amazon Web Services DynamoDB, a NoSQL database, and DynamoField also provides a front-end interactive web interface. With the flexibility of the NoSQL database, researchers can modify the database schema based on the data provided by various collaborators and contract research organizations. This framework includes functions for non-technical users, including importing and exporting data, data integration and manipulation, and performing statistical analysis. Researchers can utilize cloud computing to establish a secure NoSQL database with minimum maintenance, this also enables collaboration with others worldwide and adapt to different data-collecting strategies as their research progresses. DynamoField is implemented in Python, and it is publicly available at https://github.com/ComputationalAgronomy/DynamoField .